Efektivitas Layanan Perpustakaan Keliling dalam Mengembangkan Minat Baca Masyarakat di Dinas Perpustakaan dan Kearsipan Kota Sibolga - Juwita, Rizka; Nurhayani, Nurhayani; Yasmin, Nabila (Al-DYAS, 2024)
This research discusses the effectiveness of mobile library services in developing people's reading interest in the Sibolga City Library and Archives Service. The aim of this research is to find out whether the mobile library service at the Sibolga City Library and Archives Service is effective enough in developing people's interest in reading in Sibolga City. This research uses descriptive research with a qualitative approach. Data collection methods use observation, interviews and documentation, while technical data analysis is carried out in 3 (three) ways, namely data triangulation, method triangulation and source triangulation. The results of this research show that the effectiveness of the mobile library service in developing people's interest in reading in the Sibolga city library and archives service has gone quite well, this can be seen in real conditions after the researchers conducted observations and interviews, which can be seen based on the public's fairly good response, and the enthusiasm of children who always welcome mobile library visits to their schools. Factors that influence mobile library services in developing people's reading interest in the Sibolga City Library and Archives Service, namely book collections, users/readers, librarians on duty, and the mobile library facilities provided are supporting factors. Meanwhile, the inhibiting factors are in terms of funding, as well as inadequate facilities and infrastructure for the 17 sub-districts which are visiting points for mobile libraries for the Sibolga city library and archives service.